Polysaccharides in Agro-Industrial Biomass Residues - Souza, Márcio Araújo de; Vilas-Boas, Isis Tavares; Leite-da-Silva, Jôse Maria; Abrahão, Pérsia do Nascimento; Teixeira-Costa, Barbara E.; Veiga-Junior, Valdir F. (Polysaccharides, 2022)
The large-scale industrial use of polysaccharides to obtain energy is one of the most discussed subjects in science. However, modern concepts of biorefinery have promoted the diversification of the use of these polymers in several bioproducts incorporating concepts of sustainability and the circular economy. This work summarizes the major sources of agro-industrial residues, physico-chemical properties, and recent application trends of cellulose, chitin, hyaluronic acid, inulin, and pectin. These macromolecules were selected due to their industrial importance and valuable functional and biological applications that have aroused market interests, such as for the production of medicines, cosmetics, and sustainable packaging. Estimations of global industrial residue production based on major crop data from the United States Department of Agriculture were performed for cellulose content from maize, rice, and wheat, showing that these residues may contain up to 18%, 44%, and 35% of cellulose and 45%, 22%, and 22% of hemicellulose, respectively. The United States (~32%), China (~20%), and the European Union (~18%) are the main countries producing cellulose and hemicellulose-rich residues from maize, rice, and wheat crops, respectively. Pectin and inulin are commonly obtained from fruit (~30%) and vegetable (~28%) residues, while chitin and hyaluronic acid are primarily found in animal waste, e.g., seafood (~3%) and poultry (~4%).